1999
DOI: 10.1046/j.1365-246x.1999.00788.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of potential field data in the wavelet domain

Abstract: Various Green’s functions occurring in Poisson potential field theory can be used to construct non‐orthogonal, non‐compact, continuous wavelets. Such a construction leads to relations between the horizontal derivatives of geophysical field measurements at all heights, and the wavelet transform of the zero height field. The resulting theory lends itself to a number of applications in the processing of potential field data. Some simple, synthetic examples in two dimensions illustrate one inversion approach based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
122
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 225 publications
(141 citation statements)
references
References 20 publications
1
122
0
1
Order By: Relevance
“…[28] Let us first illustrate the multipolar series from equation (20) in case of the wavelet transform, W y 1 G jgz (b, a), of the vertical component of the gravity field, g z (h, z) = À@V(h, z)/@z, measured at level z = 0 as introduced by Hornby et al [1999]:…”
Section: Wavelet Coefficients Of Hornby Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…[28] Let us first illustrate the multipolar series from equation (20) in case of the wavelet transform, W y 1 G jgz (b, a), of the vertical component of the gravity field, g z (h, z) = À@V(h, z)/@z, measured at level z = 0 as introduced by Hornby et al [1999]:…”
Section: Wavelet Coefficients Of Hornby Et Almentioning
confidence: 99%
“…Here, we have B 2 0 6 ¼0 and B 2 2 = 0. The horizontal gradient wavelet coefficients as introduced by Hornby et al [1999] are given in equation (25) with series expansion given in equation (B3). From cylindrical symmetry, which implies B 2 2 = 0, this can be simplified at large distance r = ffiffiffiffiffiffiffiffiffiffiffiffiffiffi r 2 þ z 2 a p , where r = ffiffiffiffiffiffiffiffiffiffiffiffiffiffi x 2 þ y 2 p and z a = z 0 + a:…”
Section: Appendix C: Horizontal Wavelet Coefficientsmentioning
confidence: 99%
“…Mallat & Zhong, 1992). By applying this approach to potential field theory, Hornby et al (1999) have shown that, with the choice of an appropriate wavelet, derived from Green's function of gravitational acceleration, the measured potential field or its spatial derivatives can be treated as a wavelet transform of the source distribution.…”
Section: Conceptual Basis Of Multiscale Edge Analysismentioning
confidence: 99%
“…The detection and visualisation of these irregularities at different scales (multiscale edges) can greatly enhance the interpretation of potential field data in terms of the 3D geology (Hornby, et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation